2014
DOI: 10.1093/carcin/bgu032
|View full text |Cite
|
Sign up to set email alerts
|

miR-135a leads to cervical cancer cell transformation through regulation of β-catenin via a SIAH1-dependent ubiquitin proteosomal pathway

Abstract: Human papillomaviruses (HPVs) is the principal etiological agent of cervical cancer (CC). However, exposure to the high-risk type HPV alone is insufficient for tumor formation, and additional factors are required for the HPV-infected cells to become tumorigenic. Dysregulated microRNAs (miRNAs) expression is frequently observed in cancer but their roles in the formation of CC have not been fully revealed. In this study, we compared the expression of miR-135a in laser capture microdissected cervical specimens an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 54 publications
0
40
0
1
Order By: Relevance
“…Previous studies have shown that miR-135a is involved in cancer development and metastasis [27,28]. miR-135a inhibits cell proliferation by targeting BMI1 in pancreatic ductal adenocarcinoma [29].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that miR-135a is involved in cancer development and metastasis [27,28]. miR-135a inhibits cell proliferation by targeting BMI1 in pancreatic ductal adenocarcinoma [29].…”
Section: Discussionmentioning
confidence: 98%
“…Table 1 shows a summary of these findings, including miRNAs that have been shown to be regulated directly by E7. Other miRNAs have been shown to be regulated by HPV but the specific contribution of E7 (vs. the other viral oncogenes) is not yet known (Martinez, Gardiner et al 2008; Wang, Wang et al 2009; Bonnet, Tatari et al 2010; McKenna, McDade et al 2010; Jung, Phillips et al 2014; Leung, Deng et al 2014; Liu, Gao et al 2014; McKenna, Patel et al 2014; Zheng, Liu et al 2015; Liu, Zhang et al 2016). Only a few of these miRNAs are yet known to have a clear impact on the viral life cycle or on cancer development.…”
Section: Micrornasmentioning
confidence: 99%
“…Siah ligases regulate the ubiquitination and proteasomal degradation of several proteins that are important in a variety of signaling pathways, including transcriptional regulators (Tiedt et al , 2001; Zhang et al , 1998), membrane receptors (Liani et al , 2004; Winter et al , 2008), a microtubule-associated motor protein (Linares-Cruz et al , 1998), and other proteins (Tan et al , 2014). Studies have suggested that Siah plays important roles in a variety of biological processes including cell proliferation, migration, axon guidance, and development (Gutierrez et al , 2006; Hu et al , 1999; Lee et al , 2008; Leung et al , 2014; Lorick et al , 1999; Xu et al , 2006b). In addition, Siah plays a critical role in the induction of apoptosis and tumor suppression (Nemani et al , 1996).…”
Section: Introductionmentioning
confidence: 99%